Interactive museum of science and technology as an element of interdisciplinary learning and quality education in the Tacna Region - Hervas Espinoza, Consuelo Katherine (2016)
Today,  science and   technology have become an integral part of culture and both formal structures (school, university, etc.) and non-formal settings (media, museums, etc.) agree their aim of training scientific thinking of citizenship to the potential of both to the economic welfare of society. Objective: Develop the architectural project "Interactive Museum of Science and Technology - Tacna Region", in order to complement the scientific and technological education tacneña student population. Methodology: The methodology used was descriptive research - Explanatory: Results: As a result of an architectural research project considering the respective foundation it was developed. Conclusion: The importance of education in science and technology is exposed on the importance of them in the development of civilizations in the quality of life of man has been progressing with the passing of the years; while traditional museum concept has evolved, culminating in the type of science and technology center we know today. Therefore, the proposal of a museum of this nature is endorsed in the global context and purpose for the population emphasize the role of knowledge as a driver of development of modern societies.